Who Will Care For Us? : Long-Term Care and the Long-Term Workforce - Osterman, Paul (Book collections on Project MUSE., 2017)
The number of elderly and disabled adults who require assistance with day-to-day activities is expected to double over the next twenty-five years. As a result, direct care workers such as home care aides and certified nursing assistants (CNAs) will become essential to many more families. Yet, these workers tend to be low-paid, poorly trained, and receive little respect. Is such a workforce capable of addressing the needs of our aging population? In Who Will Care for Us? economist Paul Osterman assesses the challenges facing the long-term care industry. He presents an innovative policy agenda that reconceives direct care workers' work roles and would improve both the quality of their jobs and the quality of elder care. As the baby boom generation ages, Who Will Care for Us? demonstrates the importance of restructuring the long-term care industry and establishing a new relationship between direct care workers, patients, and the medical system. -- from back cover.